Dinamika Konflik Tata Kelola Perbatasan Indonesia-Timor Leste: Analisis Koordinasi Lintas Negara Dalam Perspektif Integrated Border Management (IBM) - Aprilia Soga; Valdisa Viesta Brata (PT. Data Jaringan Visual Indonesia (Djava), 2026)
This study examines the dynamics of conflict and border governance between Indonesia and Timor-Leste from the perspective of Integrated Border Management (IBM). Border conflicts in this region are not only related to territorial delimitation but are also influenced by historical, social, cultural, and political factors, particularly customary land disputes among border communities. The colonial legacy of the Dutch and Portuguese created inconsistencies between formal state boundaries and the social realities of local communities that maintain cross-border kinship relations and communal customary land ownership systems. This research employs a descriptive qualitative method through literature studies and policy analysis to examine the implementation of border governance and the effectiveness of cross-border coordination within the IBM framework. The findings indicate that although Indonesia and Timor-Leste have established various regulations and bilateral cooperation mechanisms such as Law Number 43 of 2008, the National Border Management Agency (BNPP), and the Joint Border Committee (JBC), their implementation still faces significant challenges, including institutional fragmentation, weak policy synchronization, and the dominance of statecentered security approaches that insufficiently accommodate the social realities of indigenous communities. The study also reveals that compared to Indonesia’s border governance with Singapore, Malaysia, Brunei Darussalam, and Australia, the implementation of IBM in the Indonesia-Timor-Leste border area demonstrates strengths in socio-cultural approaches and indigenous community participation, but remains weak in institutional integration, technological capacity, and crossborder coordination. Therefore, strengthening intersectoral coordination, policy harmonization, and local community participation is essential to achieving more effective, inclusive, and sustainable border governance. Keywords: border conflict, customary land, Indonesia-TimorLeste, border governance, Integrated Border Management (IBM)